INFLUENCE OF UPPER-BODY EXERCISE ORDER ON MUSCLE DAMAGE IN UNTRAINED MEN - Sotoode Kazem; Mirzaei Bahman; Rahmani-Nia Farhad (Physical Education of Students)
Aim : The purpose of this study was to examine acute muscle damage after different sequences of an upper-body resistance exercise session. Methods : Twelve untrained men completed two sessions (three sets; 80% one repetition maximum; two min passive rest between sets) of the same exercises in opposite sequences (larger to smaller vs. smaller to larger muscle group exercises). For each session, serum creatine kinase (CK) concentrations were measured before exercise (pre) and 24, 48 hours after each sequence (24P, 48P). Results: Within sequence (larger to smaller muscle-group exercises), significant differences in CK concentrations were demonstrated between most time points (P0.05). Conclusion: These results suggest that muscle damage was similar between sequences (larger to smaller vs. smaller to larger muscle-group exercises).